Pengaruh Model Problem Based Learning Terhadap Motivasi dan Hasil Belajar IPS Pada Siswa Sekolah Dasar di Maluku Tenggara - Hempri Alfred Kirwelakubun; I Idawati; N Nursalam (Universitas Sarjanawiyata Tamansiswa, 2023)
This research uses quantitative research with the type of quasi experiment. aims to determine the effect of the problem-based learning model on student motivation and learning outcomes. The design used was Posttest Only Control Group Design. This research was conducted in the fifth grade of elementary school in gugus I Kecamatan Kei Kecil Kabupaten Maluku Tenggara, even semester of 2022/2023 academic year. The population in this study were all students in elementary schools in cluster I Kei Kecil District, Southeast Maluku Regency. The sampling technique in this study used the Simple Random Sampling technique. The sample in this study in the experimental class was SD Inpres Watdek with 35 students and the control class was SD Inpres Ohoijang with 34 students. The research instruments used were observation sheets, questionnaires, and learning outcomes tests. Data analysis techniques using descriptive statistics and inferential statistics. Descriptive research results of social studies learning outcomes of grade V elementary school Gugus I Kei Kecil District Southeast Maluku Regency in the experimental group using Problem Based Learning Model is better than the control group without using Problem Based Learning Model. The results of inferential research, namely: 1) There is an effect of Problem Based Learning (PBL) learning model on learning motivation of fifth grade students of elementary school cluster I Kei Kecil sub-district, Southeast Maluku Regency, 2) there is an effect of Problem Based Learning (PBL) learning model on social studies learning outcomes of fifth grade students of elementary school cluster I Kei Kecil sub-district, Southeast Maluku Regency, 3) there is an effect of Problem Based Learning (PBL) learning model on motivation and social studies learning outcomes of fifth grade students of elementary school gugus I Kecamatan Kei Kecil Kabupaten Maluku Tenggara.